A qualitative study of Black adults' perceptions of virtual visits in oncology care. Issue 28 (1st October 2022) - Lafata, Jennifer Elston; Tam, Samantha; Neslund-Dudas, Christine; Barrett, Amy; Fridman, Ilona; Barrow, Lauren CJ; Kinlaw, Alan C; Middlebrooks, William; Puviindran, Praveen; Royce, Trevor Joseph; Smith, Angela B.; Stein, Jacob Newton; et al.
Abstract : 174 Background: During the COVID-19 pandemic, many oncology practices began offering virtual visits via video and/or telephone. How such visits are perceived by Black adults receiving cancer care, a category of patients often facing access barriers and poorer outcomes, is not known. We elicited Black patients' perceptions of oncology virtual visits. Methods: We conducted in-depth, semi-structured telephone interviews with Black adults aged ≥21 years who received oncology care between 6/1/19 - 3/20/21 for head & neck cancer, prostate cancer, and multiple myeloma within two US-based academic health systems. The interview guide elicited perceptions within predefined themes (e.g., ease of use, usefulness, communication quality, appropriateness). Interviews were audio-recorded, transcribed verbatim, and coded for a priori themes and new ones identified during data immersion. One trained research assistant coded all transcripts, using Atlas.ti for data management. Results: Forty-nine Black adults diagnosed with cancer completed an interview between 9/2021 and 2/2022 (n = 16 head & neck, n = 16 prostate, n = 17 multiple myeloma); mean age 62 years (range: 26-79), 55% male, and 59% reported ever having a virtual visit (n = 21 experienced video virtual visit(s), n = 8 telephone only). Perceptions of virtual visits varied. Some expressed a desire for continued use and noted advantages, including factors associated with the comfort and convenience of being home and not needing to travel (e.g., not needing to get up and dressed; reduced time and gas/parking costs). Others emphatically indicated preferring in-person visits due to the face-to-face/one-on-one/person-to-person interaction. Those with positive perceptions endorsed similarities between information exchanges, communication, and physician knowledge in in-person compared to virtual visits, but often noted insurance coverage, working technology and the need for clinical appropriateness (e.g., "it was just a follow up visit;" "I didn't need any labs") as foundational. Those expressing concerns discussed the inability for vital signs assessment/physical exams/laboratory testing, and raised concerns regarding interpersonal communication, including the inability to be physically present with one another and assess each other's body language. For some respondents this led to concerns about trust/honesty and physicians being distracted and/or missing something during the visit. Technology-related obstacles (e.g., confidence and connectivity) when experienced were reported as overcome with assistance or via switching to telephone. Conclusions: We found Black adults with cancer generally receptive to virtual visits and that telephone-only options increased access. Virtual visit acceptability among Black adults may be enhanced by improved interpersonal connectedness during visits, technology support, and patient-centered scheduling options.